Exploring public perception of solar radiation management - Christine Merk; Gert Pönitzsch; Carola Kniebes; Katrin Rehdanz; Ulrich Schmidt (Kiel Institute for the World Economy (IfW), 2014)
Solar radiation management (SRM) could quickly offset global warming caused by anthropogenic greenhouse gas emissions. Because SRM would have global side effects, it raises not only technological but also political and social concerns. Therefore, SRM research should be accompanied by a global debate that incorporates public perception and concerns into the development and governance of the technology. Our paper provides insight into public perception and explores its underlying patterns using a survey conducted in Germany. The data reveal a differentiated picture. Laboratory research on SRM is broadly approved, whereas field research is much less approved. Immediate deployment is largely rejected. The acceptance of the technology is associated with the belief that climate change is a severe problem and that humans will eventually be able to control nature. It is also determined by the levels of trust in scientists and firms. Among the strongest objections against the technology is the belief that humans should not manipulate nature in the way SRM would. The actual public perception of SRM will, however, evolve along with the ongoing debate between the public, experts, and policymakers.
Keywords: Q54; D19; H43; 330; Climate Engineering; Geoengineering; Solar Radiation Management; Climate Change; Public Opinion; Survey